Improved characterization of Feshbach resonances and interaction potentials between 23Na and 87Rb atoms - Guo, Zhichao; Jia, Fan; Zhu, Bing; Li, Lintao; Hutson, Jeremy M.; Wang, Dajun (Physical review, 2022)
The ultracold mixture of 23Na and 87Rb atoms has become an important system for investigating physics in Bose-Bose atomic mixtures and for forming ultracold ground-state polar molecules. In this work, we provide an improved characterization of the most commonly used Feshbach resonance near 347.64 G between 23Na and 87Rb in their absolute ground states. We form Feshbach molecules using this resonance and measure their binding energies by dissociating them via magnetic-field modulation. We use the binding energies to refine the singlet and triplet potential-energy curves, using coupled-channel bound-state calculations. We then use coupled-channel scattering calculations on the resulting potentials to produce a high-precision mapping between magnetic field and scattering length. We also observe ten additional s-wave Feshbach resonances for 23Na and 87Rb in different combinations of Zeeman sublevels of the F=1 hyperfine states. Some of the resonances show two-body inelastic decay due to spin exchange. We compare the resonance properties with coupled-channel scattering calculations that full take account of inelastic properties.